A Customized Transportation Intervention for Persons with Visual Impairments. (July 2017) - Crudden, Adele; Antonelli, Karla; O'Mally, Jamie
Introduction: Transportation can be an employment barrier for persons with disabilities, particularly those with visual impairments. A customized transportation intervention for people with visual impairments, based on concepts associated with customized employment, was devised, implemented, and evaluated. Methods: A pretest and posttest intervention and comparison group design evaluated changes in participants' social problem-solving skills, transportation self-efficacy, and transportation knowledge. Participants worked with a transportation coordinator to plan and secure work-related transportation. Surveys assessed participant satisfaction with the intervention. Results: The intervention group had significantly higher scores for social problem-solving skills at posttest after considering pretest scores. The intervention group responded favorably to measures of satisfaction with the intervention. Discussion: The customized transportation intervention had a positive effect on social problem-solving skills and the participants were satisfied with the intervention, although the impact of the intervention on employment outcomes remains unclear. Attrition in the study and lack of a random sample mean the results must be interpreted with caution. Implications for practitioners: Engaging individuals with visual impairments in discussions about transportation to work may educate them about new options or assist them in thinking of unexplored options. Persons who appear to have good problem-solving skills and confidence in their abilities may still benefit from these discussions.